Effect of Friction Coefficient on Relative Slippage of Fuel Cell Stack under Mechanical Impact Condition. (1st February 2018) - Hou, Yongping; Wang, Leiqi; Zhang, Jianwen; Hao, Dong
Abstract : A simplified finite element model for large polymer electrolyte membrane fuel cell (PEMFC) stack consisting of ten cells is established in order to investigate the internal structure deformation. It is found that the interface slippage occurs when the bipolar plate (BP) and membrane electrode assembly (MEA) are subjected to vertical impact acceleration. Based on this three-dimensional model, the influence of the friction coefficient between BP and MEA on the relative slippage can be analyzed efficiently. The division layer of relative slippage is found and its vibration rule is discussed. It is observed that increasing the magnitude of impact vibration has most significant effect on the movement of the division layer, and the two variables are linearly related when impact acceleration is greater than 5 g. This work provides important insight into the choice of the friction coefficient.